Comparison of Different Risk Factors and Coronary Angiographic Profile in Younger and Older Patients with Ischeamic Heart Disease (Cardiovascular Journal, 2015)
Background: Due to socio-economic improvement and changes in the life style, ischeamic heart disease is becoming a major burden to our health care system. In recent years, the incidence is increasing among younger age groups as well.Methods: A total of 120 patients with ischeamic heart disease admitted for coronary angiogram were included in the study and were divided into two groups. Among them, 60 younger patients were in Group-I (d 40 years of age); 60 older patients in Group-II (>40 years of age). We compared demographic profiles, different risk factors and angiographic profiles between two age groups.Results: Among the common risk factors, smoking (63.3% vs 40%, p=0.011) & family history of ischeamic heart disease (21.7% vs 8.3%, p=0.040) were more common in younger group. Whereas, hypertension (41.7% vs 65.0%, p=0.010) and DM (18.3% vs 36.7%, p=0.024) were more common in older patients. Serum Homocysteine level was found significantly higher in younger patients (30.0% vs 13.3%, p=0.026). In group-I. coronary angiography revealed normal coronaries in 15 patients (25%), single vessel disease in 29 (48.3%) and multi-vessel disease in 16 patients (26.6%). Whereas, 40(66.6%) patients in group-II were found to have multi-vessel disease and 2 of them had significant left main coronary disease. However, young patients who had high serum homocysteine level showed more angiographic severity than older patients.Conclusion: There are significant differences in the clinical, biochemical and angiographic profile of young patients with ischeamic heart disease as compared to older patients. Young patients with ischeamic heart disease has got less angiographic severity, except in those with high serum homocysteine level.Cardiovasc. j. 2015; 8(1): 23-29